Forgiveness Therapy to Maintain Family Resistance in Muslim Communities in Tanjungkarang Jati Kudus Village - Muzdalifah, Muzdalifah; Istianah, Istianah (Universitas Islam Negeri Sunan Kudus, 2025)
Divorce in Indonesia has increased from year to year. Based on data from the BKKBN National Population and Family Planning Agency, there will be 580,000 divorces in 2021 and in 2015 the number of divorces will not reach 400,000. This phenomenon shows that modern humans lack the spiritual intelligence that is used to maintain family resilience. One of the spiritually intelligent attitudes is to have a forgiving attitude. This study explores forgiveness as Islamic psychotherapy in maintaining family resilience in the community in Tanjungkarang Village, Jati District, Kudus Regency. The method used in this study is a qualitative method with a phenomenological approach. The research data was obtained from interviews, observations and documentation with 5 informants. The data validity test was carried out by triangulation, namely source triangulation, time triangulation, and technical triangulation. The results of this study indicate that in the midst of the Covid-19 pandemic, the people of Tanjungkarang Village were able to go through difficulties after difficulties in a wise way. Armed with religiosity which is reflected in strong faith, they are able to control the emotions of sadness and anger that are raging. Spiritual intelligence is manifested in the behavior of forgiving partners or other family members. This forgiveness therapy is a way out in maintaining family resilience, so as to create a harmonious family atmosphere, communicate openly with each other and finally find solutions to problems that befall the family.